Agama di Tengah Jaring-jaring Dunia Modern - Hamdi, Ahmad Zainul (Religió: Jurnal Studi Agama-agama, 2013)
Modernism believes that reason will eventually push over religion. Knowledge is considered capable to answer various mysteries that have enforced human to rely on religion. Modernism then is marked by the world that is more unified for the exchanging information stream and economical material. The transnational company and information technology play a pivotal role in shaping into global village. In this circumstance, religion deals with such unbelievable challenge. Religion which claims as the savior of human life is finally replaced by media. But, since 70s decade, a kind of new religious movement tries to challenge this modernization flow. This is what so called religious fundamentalism. This movement leans everything on the holy scripture as the only truth; therefore, it has exclusive and militant character. If modernism is suspected as the one that has thought out any kind of human crisis, then, does religion provide the solution? Although religion is expected to answer all crisis of modernity, its irrationality and exclusivism do not fit with modernism. Religion that is needed by modern society is religion that could be heard by modern ear and in the same time could affirm the affection to human being. Rationalism without love will drag people in a tragic humanism.